Optimización de un banco de pruebas hidráulicas para analizar las curvas características de impulsores de bombas radiales. - Jiménez Jiménez, Byron José (2016)
The present project consists in optimize a bank of hydraulic tests for the Energy Laboratory and Fluids of the Electromechanical Engineering career, for the analysis of functionality of different types of semi-open impellers radial type, in its development was considered and selected the bibliography concerning the topic, methodologies both of design impellers as of hydraulic networks, with the finality of observe the behavior of the hydraulic assembly with the different types of impellers, through the different curves of functionality. Finally was elaborated a manual that guides the student to the correct functioning and manipulation hydraulic bench. Completed the research project, in an effort to evaluate the operation practical-academic of the bank, was designed and validated a practice applicable the same, with students of ninth module of the career of electromechanical engineering of the academic period September 2015 / March 2016.